Morphometric parameters of esophageal mucous in young people with gastroesophageal reflux disease and autoimmune thyroiditis - Zhelezniakova, Natalia; Gargin, Vitaliy; Bocharova, Tetiana; Pasiieshvili, Tamara; Pasiieshvili, Liudmyla (My University, 2022)
Background & objectives: Gastroesophageal reflux disease (GERD) takes one of the leading positions in internal organs` pathology with comorbidity. Objective of our work was evaluation of morphometric parameters of the esophageal mucous membrane in young people with GERD and autoimmune thyroiditis (AIT). Methods: Patients with GERD and AIT (main group) and 45 people with isolated GERD (comparison group) matched for age, gender, and social status were examined. The mean age in the groups was 21.9 ± 2.7 and 21.2 ± 2.4 years. Morphometric parameters were obtained (total thickness of the epithelium, basal layer thickness, the height of connective tissue papillae, and intercellular space). Results: The histological study showed that in patients with GERD and AIT all the morphometric parameters studied had a significantly more severe course and exceeded similar indicators of the group with isolated GERD: epithelium total thickness 319.3±9.1 μm against 286.1±8.2 μm (p<0.01), epithelium basal layer thickness 79.6±3.2 μm versus 49.7±2.1 μm (p<0.01), connective tissue papillae height 224.8±7.3 μm against 172.7±4.6 μm (p<0.01), intercellular space 1.55±0.11 μm versus 1.12±0.09 μm (p<0.01). Considerable aggravation of the deviations in patients with AIT may reflect the involvement of an additional autoimmune inflammatory component in the pathological process. Conclusion: GERD and euthyroid AIT comorbidity in the student population is accompanied by statistically more pronounced disorganization of esophageal mucosal epithelium compared with isolated GERD. The obtained data allow us to consider concomitant AIT as an unfavorable prognostic factor in the progression of GERD in the student population.
Keywords: esophageal mucous; gastroesophageal reflux disease; GERD; autoimmune thyroiditis